2023
DOI: 10.4103/aja202352
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone replacement therapy and vascular thromboembolic events: a systematic review and meta-analysis

Rossella Cannarella,
Carmelo Gusmano,
Claudia Leanza
et al.

Abstract: To evaluate the relationship between testosterone replacement therapy (TRT) and arterial and/or venous thrombosis in patients with pre-treatment total testosterone (TT) <12 nmol l−1, we performed a meta-analysis following the Population Intervention Comparison Outcome model. Population: men with TT <12 nmol l−1 or clear mention of hypogonadism in the inclusion criteria of patients; intervention: TRT; comparison: placebo or no therapy; outcomes: arterial thrombotic events (stroke, myocardial infarction [M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…Prior research from the 1990s has shown that androgens can increase the human platelet thromboxane A2 receptor density and formation [ 6 ]. In January 2014, the Food and Drug Administration issued a warning regarding the use of TRT due to the increased risk of stroke and myocardial infarction [ 7 , 8 ]. The Harvard Medical School issued a statement directly citing an increased risk for blood clots when using testosterone replacement therapy for low levels [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research from the 1990s has shown that androgens can increase the human platelet thromboxane A2 receptor density and formation [ 6 ]. In January 2014, the Food and Drug Administration issued a warning regarding the use of TRT due to the increased risk of stroke and myocardial infarction [ 7 , 8 ]. The Harvard Medical School issued a statement directly citing an increased risk for blood clots when using testosterone replacement therapy for low levels [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies using meta-analysis on men with low testosterone levels who used TRT found that the observational data did not show a correlation; however, the review showed a need for more research as the analysis showed a lack of randomized controlled data [ 7 ]. Most recently, the TRAVERSE trial showed that TRT in men with hypogonadism with preexisting cardiovascular risk was non-inferior to a placebo [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In men with type 2 diabetes and hypogonadism TRT resulted in a decrease in left ventricular mass and improvement in diastolic function [25] . The potential mechanisms underlying these effects on myocardial remodeling may involve the modulation of various signaling pathways, including the RAAS, transforming growth factor-beta (TGF-β), and matrix metalloproteinases (MMPs) [22,24], leading to a reduction in angiotensin II levels and subsequent improvements in endothelial function, vasodilation, and myocardial remodeling [22,23].…”
Section: Secondary Outcomes: Effect Of Trt On Other Cardiovascular Ri...mentioning
confidence: 95%
“…• No Increased Risk: Multiple studies, including systematic reviews and meta-analyses, concluded that TRT was not linked to an increased risk of thromboembolic events ( [25,31]).…”
Section: Hormone Levelsmentioning
confidence: 99%
See 1 more Smart Citation